The manifestation of death as seen in Paul Kalanithi’s When Breath Becomes Air: A psychological approach - Arilia Triyoga; Apriyana Kartika Putri (Universitas Ahmad Dahlan)
When Breath Becomes Air was written by Paul Kalanithi. Death is the major thing discussed in the novel. This research investigated the manifestation of death in the novel When Breath Becomes Air by Paul Kalanithi. Perspective and attitude are the manifestation of death. It gives an impact on the main character’s life. The research proves that someone who is dying will experience a change of feeling and develop two attitudes (positive and negative). Negative attitudes include kind’s fear of death, and the positive attitudes are about what makes life worth living in spite of suffering and death anxiety.